O-OGC02 Stage Migration in Newly Diagnosed Oesophago-gastric Cancer during the first wave of COVID-19 Pandemic. (16th December 2021) - Khan, Khurram; Gall, Lewis; Chuntamongkol, Rongkagorn; McCollum, Catherine; Dreyer, Stephan; Craig, Carol; MacKay, Colin; Macdonald, Andrew; Forshaw, Matthew
Abstract: Background: Covid-19 has significantly disrupted elective and emergency health care provision including cancer care within the UK. The aim of the study was to investigate the impact of the pandemic on the staging of oesophago-gastric cancers at presentation, determine the time delay in performing gastroscopy and the multidisciplinary team (MDT) treatment outcomes. Methods: A retrospective cohort study of all newly diagnosed oesophago-gastric cancers (adenocarcinoma and squamous cell carcinoma) in a single regional MDT was performed between 1st October 2019 and 30th September 2020. Electronic records were interrogated and patients dichotomised into two groups with those presenting before the introduction of the UK national lockdown of 23 rd March 2020 compared to those presenting post-lockdown. Results: 349 new oesophago-gastric cancer patients were discussed in the MDT (192 pre-lockdown versus 157 post-lockdown). Demographics were evenly matched between the two groups. More patients presented as an emergency admission post-lockdown (28.0% vs 12.5%, p < 0.001). Median waiting time for gastroscopy was longer post-lockdown (23 vs 14 days, p = 0.035). Metastatic disease at presentation was more frequent post-lockdown (47.8% vs 33.3%, p = 0.008). Overall, more patients had a palliative rather than curative treatment intent post-lockdown (71.3% vs 57.8%, p = 0.005). Conclusions: The Covid-19 pandemic has had a significant negative effect on the stage of oesophago-gastric cancers at presentation. This has translated into more patients receiving palliative treatment and ultimately having a poorer prognosis. This study highlights the importance of maintaining cancer services during the Covid-19 pandemic.